Ansambl aktorski - HENDRYKOWSKI, MAREK (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Actors’ ensemble This article analyses how actors’ ensembles function as an alternative to the star system of actors’ participation in film.